The Influence of the Model Problem Based Instruction On Mathematical Problem-Solving Skills of Students On the Material Perform the Operation Form of Algebra - Rina Oktaviyanthi (CV. AFDIFAL MAJU BERKAH, 2021)
perform the operation form of the algebra. The purpose of this study is to determine whether the ability of mathematical problem solving of students who obtained learning using the model of Problem Based Instruction is better than on mathematics problem solving ability of students who obtained learning using the conventional method of learning and how students ' attitudes towards learning mathematics using the model of Problem Based Instruction. The instruments used are : (1) Test the ability of early mathematics, (2) Test the ability of mathematical problem solving, (3) the response of students, (4) the observation Sheet. The instrument has met the terms validity and reliability coefficient of r_xy= 0,86 and t_hitung= 9,383. This type of research is quasi-experiment. Sample experiment 32 students, a control sample of 32 students random sampling. The object of research: problem-solving abilities. The research Data the initial test, final test and questionnaire of students ' attitudes.Of the research problem solving obtained F_(count )= 8,79 > F_(table )= 4,15 there are differences in the improvement of mathematics problem solving ability of students who are given the PBI compared with students who were given the PMK. Conclusion : There is the influence of problem-solving ability of mathematics students who received problem-based learning model (Problem Based Intruction) is better than the mathematics problem solving ability of students who obtain a model of conventional teaching.